2022
DOI: 10.15586/aei.v50isp2.722
|View full text |Cite
|
Sign up to set email alerts
|

Relapse or worsening of chronic spontaneous urticaria during SARS-CoV-2 infection and vaccination in children: A telemedicine follow-up

Abstract: Background: Chronic urticaria (CU), characterized by daily wheals and/or angioedema lasting more than 6 weeks, is a common skin disease. CU is classified as spontaneous or inducible. Because of Coronavirus Disease-19 (COVID-19) pandemic, face-to-face visits were reduced, and many centers started remote consultations to minimize hospital admissions and risk for viral diffusion. Telemedicine became a valuable tool for evaluating and monitoring patients with chronic diseases, such as CU. This study aims to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Seventh, Craffert et al 1 emphasized that “there was no available literature describing new-onset CSU post–COVID-19 infection”; however, when we searched PubMed, we found a couple of studies showing that SARS-CoV-2 infection can also cause new-onset CSU. 5 We also agree with the opinion expressed by Craffert et al 1 that new-onset CSU can occur after SARS-CoV-2 infection.…”
supporting
confidence: 91%
“…Seventh, Craffert et al 1 emphasized that “there was no available literature describing new-onset CSU post–COVID-19 infection”; however, when we searched PubMed, we found a couple of studies showing that SARS-CoV-2 infection can also cause new-onset CSU. 5 We also agree with the opinion expressed by Craffert et al 1 that new-onset CSU can occur after SARS-CoV-2 infection.…”
supporting
confidence: 91%
“…Duperrex et al [ 122 , 125 ] analyzed 862 cases of post-SARS-CoV-2 vaccine CSU cases which occurred mainly after the 3rd dose (booster) of mRNA vaccines. The overall crude incidence rate of CSU after a SARS-CoV-2 booster per 100,000 persons immunized with a booster was 24 and 19 in the two cohorts, respectively.…”
Section: Vaccines and Urticariamentioning
confidence: 99%
“…The authors also observed that fewer exacerbations happened when patients were under omalizumab therapy [ 124 , 127 ]. Likewise, Lascialfari et al [ 125 , 128 ] reported that relapse or exacerbation of urticaria after SARS-CoV-2 vaccination was observed in only 7.7% of pediatric CSU patients which lasted for less than one week. Picone et al [ 126 , 129 ] reported postvaccine urticaria to flare up in 8% of CSU patients who were well controlled under antihistamine and omalizumab treatment, while Tuchinda et al [ 127 , 130 ] reported a higher rate (15%).…”
Section: Vaccines and Urticariamentioning
confidence: 99%
“…4/26 (19.2%) cases who had COVID-19 manifested with CSU recurrence, while 1 (3.8%) had a CSU worsening/deterioration. Meanwhile, 1/26 (3.8%) vaccinated patient had a recurrence of CSU, and 1 (3.8%) had a deterioration of CSU course [7].…”
Section: Discussionmentioning
confidence: 99%